The Role of Maternal Progesterone and Estradiol Levels in Predicting the Success of Induction of Labour: A Preliminary Study: Hubungan Kadar Progesteron dan Estradiol Ibu terhadap Keberhasilan Induksi Persalinan: Suatu Studi Pendahuluan - Kanadi Sumapraja; Hilda R Badruddin (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective: to evaluate whether maternal progesterone and estradiol levels could be used to predictthe success ofinduction of labour (IOL) Methods:This cross-sectional study was conducted at the Women’s Health Clinic as well as delivery suite of Dr. Cipto Mangunkusumo Hospital during the period of May 2016 to April 2017. Blood samples of term pregnant women who were indicated for IOL wereobtainedbefore birth. Results:A total 44 subject were recruited in this study.Of these, 24 subjects had successful IOL while the other 20 subjects had IOL failure. There was no significant difference of progesterone among both groups (66,7% vs 75%, p=0,55). The estradiol levels in subjects who successfully performed induction had an average of 16,916.28 ± 2,574.75 pg/mL which did not differ significantly from the failed of induction group with estradiol levels of 14,832.24 ± 2374.47 pg/mL (p = 0,65). Conclusion:We found no significant association between both maternal progesterone and estradiol levels and the success rate of IOL. Further studies with larger sample sizes are required to confirm whether progesterone and estradiol play pivotal roles in the success of IOL. Keywords: progesterone, estradiol, induction of labour Tujuan: mengevaluasi kadar progesteron dan estradiol ibu sebagai prediktor kesuksesan induksi persalinan Metode: Penelitian ini menggunakan desain potong lintang yang berlangsung pada bulan Mei 2016 hingga April 2017 di Poliklinik dan IGD Kebidanan Rumah Sakit Umum Pusat Rujukan Nasional Cipto Mangunkusumo. Pasien hamil aterm yang dilakukan induksi persalinan dan memenuhi kriteria penelitian akan diambil sampel darah sebelum persalinan. Hasil: Dari 44 subjek yang mengikuti penelitian, 24 subjek berhasil dilakukan induksi persalinan dan 20 subjek gagal.Tidakterdapatperbedaanbermaknapadakadarprogesterone Antarakeduagrup(66,7% vs 75%, p=0,55). Kadar estradiol padapasien yang berhasildilakukaninduksimemiliki rata-rata 16.916,28 + 2.574,75pg/mL yang tidakberbedajauhdengankadar estradiol pasien yang gagalinduksiyaitu 14.832,24 + 2374,47pg/mL (p = 0,65). Kesimpulan: Tidakterdapat perbedaan bermakna antara kadar progesteron dan estradiol maternal terhadap keberhasilan induksi persalinan. Penelitian lebih lanjut dengan jumlah sampel yang lebih besar dibutuhkan untuk mengkonfirmasi hubungan ini dengan lebih baik. Kata kunci: progesteron, estradiol, induksi persalinan